(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2018)
Corporate social responsibility is one of the needful and prominent business practices of today’s scenario. Companies Practising CSR has an enhanced overall reputation and their corporate identity promotes positive culture among society. The execution of a CSR process is an important component of a company’s assets and its strategy is a competitive component in market itself which is led by company itself. This means integrating 3P’s which acts a tool of society like people, planet and profit which collaborates with(Internal and External Public) stakeholders. Overall aim is to make a positive and strong impact on society as a whole. The company’s bottom line refers to a company’s net earnings, net profit or net income. The term “bottom" explains the net income figure on a company’s income statement. Bottom line also refers to any activity that may increase/decrease net earnings. A company that has more net earnings or reducing costs cutting is said have “improving its bottom line". Most companies aim to improve their bottom lines through two simultaneous methods: growing profits through revenues and increasing efficiency through cutting costs. This paper focuses on how CSR initiative has affected the company bottom line or overall growth. It will throw light on the scenario and impact of CSR strategies followed by companies. The purpose is well defined to know the 5w’s and 1H of CSR initiatives. With various case studies we will try to answer who does CSR and how. What is the company all about, where is it located, whom it is run by, Since when it is running and how the company has implemented CSR strategy and what was the result, This paper has opted for descriptive research design. It is a scientific method which involves observing and describing the behavior of a subject without influencing it in any way. Various research methods are implemented by researches. Various case studies will be studied regarding the implementation of CSR strategy by various companies and how that has resulted and had an impact on society. As we can see that this paper has used Descriptive research design, or qualitative, various methods, include the, case study, naturalistic observation, surveys, archival research, longitudinal research, and cross-sectional research. The Scope of the research is to know the benefits of CSR schemes in India and to know whether these CSR and philanthropy activities are useful in today’s scenario for people as well as company .